Review on the Bubble Dynamics Based Cavitation Dynamics for the Negative Squeeze Motion in Lubricated Contacts - Geike, Thomas (Frontiers in Mechanical Engineering, 2020)
Simulation models for the cavitation dynamics in lubricated contacts can be roughly clustered into two groups: either without or with bubble dynamics, the first one being the standard case for most fluid film bearing calculations. The approach with bubble dynamics has been introduced to the lubrication community about 20 years ago by Someya, and it is based on the coupling of Reynolds equation and Rayleigh-Plesset equation. It has been used for journal bearings, squeeze film dampers, and it is essentially required for correct numerical calculations of the negative squeeze motion (i. e. the separation of two plates) or the oil stiction problem. More than a decade ago, in 2009, the first paper on the negative squeeze motion with bubble dynamics -- allowing numerical calculations of tensile stresses in the lubricant -- had been published. The application in mind is the simulation of mixed lubrication for rough surfaces. The negative squeeze motion is then understood as the motion of asperities (on smaller length scales). The paper at hand summarizes some of the research on the dynamics of cavitation in lubricated contacts from different research groups from the last 10 to 15 years and sketches key topics for further research on the topic. The roadmap is centered around the three key issues that remained from the previous research of the author: (a) numerical stability of the calculations for curved plates, (b) characteristic time scale for separation of plates and (c) experimental evidence for validating the calculation results.